Overview of Modern Methods and Technologies for the Well Production of High- and Extra-High-Viscous Oil - Inzir Raupov; Mikhail Rogachev; Julia Sytnik (Energies)
This paper presents a review of modern methods and technologies for extracting high- (HVO) and extra-high-viscous oil (EHVO). Special attention is given to thermal, physico-chemical, and combined enhanced oil recovery (EOR) methods based on the synergistic effect of these approaches. Theoretical aspects of these technologies, their applicability limits, and their practical implementation are considered. The article describes the main complicating factors in the extraction of HVO and EHVO using the reviewed methods, one of which is the high water cut in well production. We analyse the mechanisms of water production in HVO and EHVO fields. The paper highlights the experience of developing HVO and EHVO fields, primarily in Russia, and examines laboratory and field studies, ongoing projects, and future prospects. The authors of this paper have analysed the available literature and have provided further recommendations for studying these technologies. We hope that this work will be useful to all those interested in the challenges of oil production.